The Effect Of "Balut" Therapy Device On Knee Pain In Osteoarthritis - Niken, Niken; Kristiana, Kristiana; Dwi Febryanto (Jurnal EduHealth, 2024)
Studies Osteoarthritis is one of the degenerative elements most customarily discovered in musculoskeletal diseases; osteoarthritis is the most common motive of restricted movement and feature; the region most often affected is the knee joint (Susilawati et al., 2015). The incidence of osteoarthritis dramatically follows the growth in patient age. As many as 70% of patients elderly over sixty-five years old suffer from osteoarthritis (Suhendriyo, 2014). The major hassle skilled by osteoarthritis sufferers is constrained helpful hobbies. Osteoarthritis can also cause disturbances in purposeful activities, along with trouble on foot, lengthy distances, standing from a squatting position, going up and down stairs, and disruption in valuable activities. Pain management techniques consist of pharmacological remedies and non-pharmacological therapy. Pharmacological remedy consists of drugs, while non-pharmacological therapy includes bodily remedy, modalities, and cognitive and behavioral techniques. The physical remedy to alleviate pain consists of numerous varieties of skin stimulation (massage, nerve stimulation with transcutaneous power, acupuncture, bloodless or warmth or compresses application, and exercise). Heat utility is a simple movement that has long been regarded as a powerful technique for reducing pain or muscle spasms.Heat can be distributed through conduction (hot water bottles, wet compresses, heat). Pain from bruises, muscle spasms, and arthritis respond appropriately to warmth (Price and Wilson, 2005;1087-1088). Ginger has pharmacological results that might be efficacious as a remedy (Team Lentera, 2002; 1). This study is a quantitative observation with a move-sectional quasi-experiment layout and uses the chi-square (bivariate) statistical check. The population is all citizens of RT 05 RW XVI Tlogosari Kulon Semarang. Sampling used purposive sampling—place and time of research at RT V RW XVI Tlogosari Kulon Semarang. The research tools and substances used by researchers are the 'BALUT' (Knee Bandage) tool, which is an aggregate of the use of a knee decker and ginger compress.